Dampak Pembangunan SMPN 3 Blitar Terhadap Kinerja Lalu Lintas Sekitarnya - Miftachul Huda; Dwi Muryanto (Universitas Muhammadiyah Surabaya, 2017)
SMPN 3 Blitar it will be build on Ciliwung street. It was one of access roads to Blitar City. SMPN 3 Blitar it will be operated in 2019, then has to knowed the impact of development on the performance of traffic around it. This study aims to determine the degree of saturation of existing, operating time, and five years after SMPN 3 Blitar was operated. The analysis of this study is using Indonesian Highway Capacity Manual (IHCM). The Primary data in this study is peak hour traffic volume, intersection geometric conditions, and the cycle time for signalized intersections around the site. While the secondary data in this study is the road network, an Origin Destination (OD), the GDP, and Blitar population. The analysis was started with calculating the flow of traffic at peak hours, the capacity of the intersection, and the degree of saturation. The results of the analysis of the degree of saturation (DS) was indicated that the value of the intersection on the condition of the existing DS (2016), which has a value ≥ 0.750 is the intersection of the Ciliwung-Bendo. While the value of DS at the time of SMPN 3 Blitar operation (2019), which has a value ≥ 0.750 is the intersection of the Ciliwung-Bendo. And the value of DS at five years after SMPN 3 Blitar was operated (2021), which has a value ≥ 0.750 is the intersection of the Ciliwung-Bendo.